Density Normal Compaction Trend in the Peciko Field, Lower Kutai Basin, Indonesia - Agus M. Ramdhan; Neil R. Goulty; Stuart J. Jones; Lambok M. Hutasoit (Indonesian Journal on Geoscience, 2020)
DOI:10.17014/ijog.7.3.253-265The density normal compaction trend is the mandatory parameter in order to calculate contribution of disequilibrium compaction to overpressure, in the presence of unloading to total overpressure. In this paper, mudrock compaction behaviour is studied in the Peciko Field. The density normal compaction trend was constructed in a normally pressured section, where the temperature is <1200C, within the transformation of smectite–illite zone. The compaction trend includes not only vertical effective stress, but also diagenesis, especially smectite-illite transformation, as dependant factor for compaction, both termed as β. This compaction trend is also known as Skempton-Duta compaction model. Quardros-Linares fifth-order kinetic reaction was found that could model smectite-illite transformation in the studied area fairly well. The plot between β and smectite content shows a very good match, confirming that Skempton-Dutta compaction model is valid for the entire range of smectite-illite transformation. In the area where the density log is unavailable, the density normal compaction can be constructed from temperature history acting as a proxy for smectite-illite transformation, with some local calibration.